Job Stress, Job Burnout and Performance of Paramedics during the Covid 19 Pandemic - Putri Dian Rarastanti; Tri Siwi Agustina; Sutinah Sutinah; Arif Fatah Hidayat (Universitas STRADA Indonesia, 2021)
This study aims to analyze the influence of work stress and job burnout on the performance of health workers during the Covid-19 pandemic and analyze the influence of work stress on the performance of health workers of Aisyiyah Ponorogo General Hospital mediated by job burnout during the Covid-19 pandemic. The type of data used consists of primary data, namely data obtained from the dissemination of questionnaires and secondary data obtained from the company's internal data, journals, books and scientific articles. This study used a sample of 194 respondents who are health workers. The results of this study found that: 1) work stress has a negative and significant effect on performance in health workers; 2) work stress has a positive and significant effect on burnout in health workers; and 3) work stress has a negative and significant effect on the performance of health workers through mediation of burnout variable